Operational Performance Of PPI Paotere Makassar City - M, Andi Tenri Fada; Kurnia, Muhammad; Mallawa, Achmar (Torani Journal of Fisheries and Marine Science, 2021)
This study aims to analyze the level of operational performance and identify the possibility of upgrading the port class of PPI Paotere Makassar city. The research method case study is operational aspect, including facilities provision to evaluate the operational performance. The performance assessment is obtained by comparing the condition at PPI Paotere with the regulation stipulated by The Ministry of Maritime Affairs and Fisheries of Republic of Indonesia Regulation No.PER.08/MEN/2012 and also General Director of Capture Fisheries Decree No.432/DPT3/0T.220.D3/I/2008. The data are analyzed descriptively using table Sscoring method of fishery port type D operational performance. The result shows that the percentage of total production success 1.706,3%, ship visiting frequency 180%, ice service 2.466,7%, fuel service 272,55%, clean water service 52,98% and also port facilities availability such as administration office, international marketing, processing industry, marketing facilities, canteen, worship place, polyclinic and service post, but there are no fishing gear and ship repair facilities, spare parts supply and residence. The operational performance of PPI Paotere has a very good operational performance category that exceeds its capacity as a type D fishing port, but it is no longer possible to increase the port class due to the limited area.